FLASH SALE DAN IMPULSE BUYING KONSUMEN E-COMMERCE PADA MASA PANDEMI COVID-19 - Atrisia, Marchela Indah; Hendrayati, Heny (Journal of Business Management Education (JBME), 2021)
The Covid-19 pandemic has caused many losses in all sectors and various parties, both business actors and consumers. Due to restrictions from the government in reducing the transmission of Covid-19, some trade sectors have begun to switch from offline to digital. This makes transactions through e-commerce also increase sharply. One of the sales promotions that is often used by e-commerce platforms to increase sales is through a flash sale program. This study aims to see whether the flash sale program has an influence on impulse buying during the Covid-19 pandemic. Sampling was done through convenience sampling technique and got 119 respondents as a sample. The data analysis method used is validity test, reliability test, and simple linear regression analysis which is processed using SPSS 23. The results of the research conducted indicate that the flash sale program has an influence in increasing impulse buying.